THE EFFECT OF JOB DEMANDS AND DUAL ROLE DEMANDS ON WORK-FAMILY CONFLICT AND EMPLOYEE WELL BEING AMONG FEMALE MANUFACTURING WORKERS IN BOGOR - Elda Sintia; Hilmiana; Wa Ode Zusnita Muizu (SOSIOEDUKASI, 2026)
This paper investigates how workplace requirements and home-front obligations trigger work-family friction, while also looking at how these combined pressures shape the overall life quality of female factory workers in Bogor Regency. Driven by real-world conditions like physical exhaustion, lengthy shifts, and domestic duties, this study surveyed 182 workers through purposive sampling. Using SmartPLS 4 for partial least squares structural equation modeling, the analysis shows that job and dual-role pressures significantly pull down employee wellness and fuel work-family friction, which in turn degrades life quality. Ultimately, these results highlight that health declines among female laborers stem from a blend of occupational stress and home responsibilities, pointing to an urgent need for gender-aware corporate rules.